Library External Review Process: Conducting Effective Assessment for Self-Study Preparation - Fazal, Shafeek (Qualitative and Quantitative Methods in Libraries, 2017)
Library External review process is periodically undertaken by academic libraries to assess how well services and resources are meeting users’ needs.  This review process is focused on the library as a department and not to be confused with institutional program review. Though some libraries choose not to do this, many libraries use the external review process to gauge their operations in preparation for accreditation visit. This paper outlines the assessment activities conducted by an academic library as it prepared a comprehensive self-study document for an external review process.  Data comparison to prior self-study reports are done to highlight trends in the Library’s services and resources.